2010
DOI: 10.1213/ane.0b013e3181bdc63d
|View full text |Cite
|
Sign up to set email alerts
|

Dental Sedation by Dentists: A View From Anesthesiologists Working in Central Western Brazil

Abstract: Many anesthesiologists in Central Western Brazil do not sedate dental patients and are not confident that dentists are able to do it. Dental sedation is an issue that still needs to be clarified in this region; the respective roles of physicians and dentists need to be determined to benefit the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…There have been other studies with a similar purpose which had low response rates of 47% [33] and 16% [16]. We understand that, as in another study with Brazilian health professionals [9], factors influencing response rates might include an unwillingness to participate or lack of interest in the subject. Also, we did not include dentists who attended a RA course but did not ask for their BCD license.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…There have been other studies with a similar purpose which had low response rates of 47% [33] and 16% [16]. We understand that, as in another study with Brazilian health professionals [9], factors influencing response rates might include an unwillingness to participate or lack of interest in the subject. Also, we did not include dentists who attended a RA course but did not ask for their BCD license.…”
Section: Discussionmentioning
confidence: 88%
“…In Brazil, one study showed that 93.7% of anesthesiologists surveyed disagreed that licensed dentists are adequately prepared to provide RA after the 96-hr training course required by the BCD [9]. However, this understanding of anesthesiologists’ opposition was not a clear barrier to RA practice among Brazilian respondents, since only about half the respondents agreed that anesthesiologists’ contrary opinion on RA should limit its use by dentists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentists qualified at educational institutions can perform sedation with nitrous oxide, but the technique requires the collaboration and cooperation of the patient to wear the inhalation mask [25,26]; therefore, it was most likely not performed in the studied cases.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, the high rate of cluster 1 in non-host cities compared to host cities may suggest inadequate prescription or services to patients with other systemic conditions [24,25].…”
Section: Discussionmentioning
confidence: 99%